Mechanosensitive potassium channels in neurons projecting cardiac axons of the nodose ganglion in rats - Linz, Peter; Hutter, Eva; Ditting, Tillmann; Schiffer, Mario; Amann, Kerstin; Hilgers, Karl F.; Veelken, Roland; Rodionova, Kristina (Frontiers in Physiology, 2025)
Cardiac vagal afferent neurons, located in the nodose ganglion, play a pivotal role in cardiopulmonary reflexes that link cardiac filling states to renal sympathetic outflow and the maintenance of circulatory homeostasis. Their excitability depends on a fine balance of depolarizing and repolarizing ion fluxes, yet the contribution of mechanosensitive (MS) ion channels to this regulation remains incompletely understood. While non-selective cation channels such as Piezo1/2 are established mediators of baroreceptor function, they are not directly responsible for repolarization. In contrast, mechanosensitive potassium channels are ideally suited to terminate action potentials and thereby shape afferent signaling from the heart. We, therefore, tested the hypothesis that MS potassium channels are functionally expressed in nodose ganglion neurons with cardiac projections. Using excised-patch recordings with stepwise suction, we identified two types of MS channels. One was inhibited by extracellular gadolinium (100 µM) and exhibited a higher unitary conductance, while the other was insensitive to gadolinium and showed a lower conductance. Both channel types were predominantly selective for K+ but also permeable to Na+, with a relative K+: Na+ permeability of ∼3.3–3.4. This mixed selectivity provides sufficient depolarization to activate voltage-gated Na+ channels and thereby initiate action potential firing. Our findings provide direct evidence for the presence of MS potassium channels in cardiac vagal afferent neurons and suggest that they may contribute critically to the mechanoelectric coupling and reflex control of cardiovascular function.